Comparative study of chemical and functional-technological properties for milts of commercial fishes - Natalia V. Dementeva; Elena Yu. Voropaeva (Известия ТИНРО, 2014)
Milts are produced as food waste after processing of such raw fishes of high nutritional value as salmons, cod, and herring. Their using as a basement for food products is a perspective way of fish-processing technology development. Chemical and function-technology properties of chopped milt are investigated to determine their suitability for producing of food products, as sausages, pates, souses, and pastes and these properties are compared for the milts from salmon, cod, and herring. The milts are 3-26 % of the raw fish weight for these commercial species that is a significant amount of food waste. The milt tissue is slightly saturated by fats (coefficient of food saturation is 0.3 for all investigated fishes) and highly saturated by water, so the milt should be combined with other raw materials for increasing the food value. The milt lipids differ from the lipids of muscular tissue by high concentration of essential polyunsaturated fatty acids with five and six connections; the amount of these fatty acids is twice higher than the amount of saturated ones (49-52 % of total fatty acids). Moreover, the milt lipids have high coefficients of metabolism comparing with the lipids of muscular tissue, that’s why they are easy digested by human. The milts of all investigated fish species are distinguished by ability for fat emulsification. These high functional-technological properties allow to recommend the milts of salmons, cod and herring for high spectrum of food products, including emulsion ones.